Combined Off-Pump Coronary Artery Bypass Grafting and Lung Resection in Patients with Lung Cancer Accompanied by Coronary Artery Disease - Yeginsu,Ali (2018)
Abstract Introduction: Optimal surgical approach for the treatment of resectable lung cancer accompanied by coronary artery disease (CAD) remains a contentious issue. In this study, we present our cases that were operated simultaneously for concurrent lung cancer and CAD. Methods: Simultaneous off-pump coronary artery bypass surgery (OPCABG) and lung resection were performed on 10 patients in our clinic due to lung cancer accompanied by CAD. Demographic features of patients, operation data and postoperative results were evaluated retrospectively. Results: Mean patient age was 63.3 years (range 55-74). All patients were male. Six cases of squamous cell carcinoma, three of adenocarcinoma and one case of large cell carcinoma were diagnosed. Six patients had single-vessel CAD and 4 had two-vessel CAD. Three patients underwent OPCABG at first and then lung resection. The types of resections were one right pneumonectomy, three right upper lobectomies, one right lower lobectomy, three left upper lobectomies, and two left lower lobectomies. Reoperation was performed in one patient due to hemorrhage. One patient developed intraoperative contralateral tension pneumothorax. One patient died due to acute respiratory distress syndrome at the early postoperative period. Conclusion: Simultaneous surgery is a safe and reliable option in the treatment of selected patients with concurrent CAD and operable lung cancer.